Early Intra‐articular Corticosteroid Injection Improves Pain and Function in Adhesive Capsulitis of the Shoulder: 1‐Year Retrospective Longitudinal Study. Issue 1 (12th June 2017) - Ahn, Jung Hwan; Lee, Doo‐Hyung; Kang, Hyuncheol; Lee, Michael Y.; Kang, Dae Ryong; Yoon, Seung‐Hyun
Abstract: Background: Intra‐articular corticosteroid injection is a commonly used therapy for adhesive capsulitis, but not enough studies exist on the optimal timing of the injection. Objective: To determine whether intra‐articular corticosteroid injection has better outcomes in patients with earlier stage than later stage of adhesive capsulitis. Study Design: Retrospective longitudinal study Setting: University‐affiliated tertiary care hospital. Participants: Primary adhesive capsulitis patients (n=339) who were unresponsive to at least 1 month of conservative treatment and who had ultrasound‐guided corticosteroid injection. Interventions: Not applicable. Main Outcome Measurements: Visual analogue scale, Shoulder Pain and Disability Index, and passive range of motion (flexion, abduction, external rotation, and internal rotation and extension) were evaluated at pretreatment, month 1 and 12 after the first injection. Results: The result of the multiple regressions, which considered the main and the interaction effect of confounding variables, showed that the differences of all outcomes in both short‐term effect at month 1 and long‐term effect at month 12 are greater when the duration of pain prior to injection is shorter. Among the confounders, the injection number in the difference of internal rotation and extension between month 0 and 12 (IRE Δ(0‐12)) was statistically significant. IRE Δ(0‐12) was also greater when the pain duration was shorter, though the decrease in IRE Δ(0‐12) differed depending on the number of injections. Conclusions: Early injection improves outcomes of adhesive capsulitis at both short‐ and long‐term follow‐ups. If pain persists despite non‐invasive and conservative treatments, early injection may be considered to shorten its natural history. Level of Evidence: III